Plant-based milk in arresting caries - Rahamat, Siti Fatimah; Wan Abd Manan, Wan Nor Hayati; Shahdan, Intan Azura; Jalaludin, Anil Azura; Abllah, Zurainie (Elsevier, 2019)
Dental caries occurs due to high net demineralization that caused loss of enamel minerals. Milk has become a promising agent of remineralization for its high content of CPP-ACP. However, some individuals cannot consume milk due to their health conditions. Plant-based milk was opted as milk substitute to recover some nutritional deficiency. Some plant-based milk has high amount of calcium which suggests the ability to promote enamel remineralization. Articles regarding plant-based milk were referred from 1960s until recently and compared with remineralization mechanism of action of milk. This review explores the potential of plant-based milk in arresting caries, especially coconut milk.